WHATSAPP MOBILE TOOL IN SECOND LANGUAGE LEARNING - Nanan Abdul Manan (Indonesian EFL Journal, 2017)
This research focuses on the improvements of communicative learning skill. It uses a common technology tool of commonucation, whats application. English, as in nonnative education athmosphere, is dangerous lecture. The students of university, eventhough, have learnt English from primary school up to Senior High School, they still find difficulty in practicing and understanding English as their custom and community. The difficult one can occur as the threarthening problem in every opportunity in English practicing. Some problems are from teachers, methods, instrumets or motivation in providing English at class. WhatsApp is an application in currently technology used by many people, not exception for students at STKIP Muhammadiyah Kuningan. It gives some interesting communication among students. The tool provides many advantages in communication. In this case, WhatsApp mobile tool can support communicative learning in second language learning among students of university whether in writing and reading skills or in improving motivation to learn. English interractively is needed as the result of this lecture. The students use the application as fun and relax activities without barrier and ashamed communication. In this point, they can increase and improve their vocabularies by means of WhatsApp tool communication. This study purposes to be fully utilized WhatsApp mobile tool to improve communicative skill in English language learning.Key words: WhatsApp, second language, improving communication skill, motivation.